Material Processes in the Singaporean Online News on Forest Fires Issue - Octavia Chandra Dewi; Sutiono Mahdi (International Journal of Systemic Functional Linguistics, 2020)
A material process may show something that has been done physically between two entities, in the clauses or texts. It shows who (or what) is the actor that does the action, if possible, to the goal (or, range), as the participant in the news. This research explained the words as material processes in clauses and the function of their appearance in the online news based on its features of transitivity as part of Systemic Functional Linguistics through the contexts. A descriptive qualitative method was used to explain the processes. The material processes in the text were analyzed based on types of processes of transitivity in Systemic Functional Linguistics study. There are fifty-one material processes found in the text, consists of thirty-seven processes of doing (composed by the creative and the dispositive processes), and fourteen processes of happening. Material processes that were used in the news text show the material actions done by entities (animate or inanimate objects), written from the point of view of the news writer(s). By this research, it can be seen that material processes are very useful for text writing, such as giving more colors, drawing more interest from the readers, giving different word meaning in different contexts, and giving more meaning to the context itself.